Commercial Extruded Plant-Based Diet Lowers Circulating Levels of Trimethylamine N-Oxide (TMAO) Precursors in Healthy Dogs: A Pilot Study - Cavanaugh, Sarah M.; Cavanaugh, Ryan P.; Streeter, Renee; Vieira, Aline B.; Gilbert, Gregory E.; Ketzis, Jennifer K. (Frontiers in Veterinary Science, 2022)
Elevations in circulating trimethylamine N-oxide (TMAO) and its precursors are observed in humans and dogs with heart failure and are associated with adverse outcomes in people. Dietary intervention that reduces or excludes animal ingredients results in rapid reduction of plasma TMAO and TMAO precursors in people, but the impact of diet in dogs has not been studied. The objective of the current study was to determine the effect of diet on plasma TMAO and 2 of its precursors (choline and betaine) in dogs fed a commercial extruded plant-based diet (PBD) or a commercial extruded traditional diet (TD) containing animal and plant ingredients. Sixteen healthy adult mixed breed dogs from a university colony were enrolled in a randomized, 2-treatment, 2-period crossover weight-maintenance study. Mean (SD) age and body weight of the dogs were 2.9 years (± 1.7) and 14.5 kg (± 4.0), respectively. Eight dogs were female (3 intact, 5 spayed) and 8 dogs were male (4 intact, 4 castrated). Plasma choline, betaine and TMAO were quantified by LC-SID-MRM/MS at baseline, and after 4 weeks on each diet. Choline and betaine were also quantified in the diets. Plasma choline levels were significantly lower (P = 0.002) in dogs consuming a PBD (Mean ± SD, 6.8 μM ± 1.2 μM) compared to a TD (Mean ± SD, 7.8 μM ± 1.6 μM). Plasma betaine levels were also significantly lower (P = 0.03) in dogs consuming a PBD (Mean ± SD, 109.1 μM ± 25.3 μM) compared to a TD (Mean ± SD, 132.4 μM ± 32.5 μM). No difference (P = 0.71) in plasma TMAO was detected in dogs consuming a PBD (Median, IQR, 2.4 μM, 2.1 μM) compared to a TD (Median, IQR, 2.3 μM, 1.1 μM). Betaine content was lower in the PBD than in the TD while choline content was similar in the diets. Our findings indicate consumption of a commercial extruded PBD for 4 weeks reduces circulating levels of the TMAO precursors choline and betaine, but not TMAO, in healthy adult dogs.